Enhancing Sustainable Transparency: A Content Analysis of Sustainability Reporting in Financial vs. Non-financial Sectors - Kurniawati, Anggreni Dian; Michelle, Paullyne (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
Sustainability reporting is becoming increasingly important for companies across various industries due to the growing awareness of sustainability issues and the stakeholders demand for sustainability performance information. However, sustainability reporting practices might differ throughout industries due to their specific characteristics. This study aims to compare sustainable reporting practices in financial and non-financial industries. A descriptive qualitative approach using secondary data is chosen in which the 2022 sustainability report was produced by the top ten financial and non-financial companies listed on the Indonesia Stock Exchange. This study uses content analysis with Landrum model categories and keyword frequency to evaluate the transparency levels of financial and non-financial industries’ sustainability reporting. The findings reveal that financial industries disclose more about the environment or ecology than non-financial industries that are more business- centered. The results of this study contribute to companies improving sustainable reporting practices and helping stakeholders understand sustainability information reported by companies in different industries so that they can make better decisions.